Challenge facing Sudanese business organizations for using knowledge management system - Elshaiekh, Nour Eldin Mohamed; Woods, Peter Charles; kashif, Ahmed Ibrahim (2008)
The current century is focusing toward knowledge-based system.Knowledge is a fundamental resource for developing a knowledge-based system and it can give power to any organization. Because of that, every Sudanese organization is going to changes and is required to adapt to the changes for good results.While the field of Knowledge Management has long been studied by scholars of several disciplines, there remain significant challenges for the future.The Most people expect the economy to grow and competition to increase in Sudan.In our paper, we will focus on Challenge Facing Sudanese Business Organizations for Using Knowledge Management System.These challenges reside in Sudanese organization by both theoretical and conceptual studies inc lude; The Growth of Information and Communications Technology (ICT), Globalization, Knowledge Management and Organizational Competitiveness, Culture, The individual, Shared leadership, and others. On this paper we will use an observation and literature survey from all possible sources and formats based on knowledge management challenges.